Mice in translational neuroscience: What R we doing?. (October 2022) - Azkona, Garikoitz; Sanchez-Pernaute, Rosario
Abstract: Animal models play a pivotal role in translational neuroscience but recurrent problems in data collection, analyses, and interpretation, lack of biomarkers, and a tendency to over-reliance on mice have marred neuroscience progress, leading to one of the highest attrition rates in drug translation. Global initiatives to improve reproducibility and model selection are being implemented. Notwithstanding, mice are still the preferred animal species to model human brain disorders even when the translation has been shown to be limited. Non-human primates are better positioned to provide relevant translational information because of their higher brain complexity and homology to humans. Among others, lack of resources and formal training, strict legislation, and ethical issues may impede broad access to large animals. We propose that instead of increasingly restrictive legislation, more resources for training, education, husbandry, and data sharing are urgently needed. The creation of multidisciplinary teams, in which veterinarians need to play a key role, would be critical to improve translational efficiency. Furthermore, it is not usually acknowledged by researchers and regulators the value of comparative studies in lower species, that are instrumental in toxicology, target identification, and mechanistic studies. Overall, we highlight here the need for a conceptual shift in neuroscience research and policies to reach the patients. Highlights: Mice are the preferred animal species to model human brain disorders, but often fail in translation. Monkeys provide relevant translational information because of their higher brain complexity and homology to humans. The value of comparative studies in lower species is seldom acknowledged by researchers and regulators. We propose a conceptual shift in neuroscience research and policies to improve the translation.